Financialization of housing in Southern Europe: Policy analysis and recommendations Final report – submitted 28/01/2021 - Tulumello, Simone (2021)
This report presents the results of the study ‘Financialization of housing in Southern Europe: policy analysis and recommendations’, carried out between August and November of 2020. The study, which focuses on Portugal, Spain, Italy and Greece, is based on a comprehensive review of the scholarly literature on the financialization of housing and on a systematic collection of relevant legislation produced in the four countries. The study identifies six modes of housing financialization and several cross-cutting dimensions: 1) mortgage debt, which links the access to homeownership to finance; 2) mortgage securitization, the use of mortgage portfolios as securities/assets; 3) financialization of social rented housing; 4) financialization of market rental housing; 5) transformation of public or not-for-profit housing companies into financialized companies; 6) financialization of ‘not-for-housing housing’ (NFHH) (Donald and Roling 2019), and in particular short-term rentals (STRs) and empty housing used as investment. 7) cross-cutting issues, that is, regulations, practices and programmes that intersect the previous modes, easing the attraction and penetration of financial capital into housing systems and real estate markets. Based on this framework, the study systematizes the role of the state in housing financialization in Southern Europe, observing a number of ‘waves’ of housing financialization.